Retroperitoneal fibrosis in presence of autoimmune coagulation factor XIII deficiency result in recurrent critical post-operative hemorrhage: a case report and molecular research with new insights - Matsushita, Tomonori; Tachibana, Mitsuhiro; Nakagawa, Hiromichi; Goto, Shuhei; Nishizawa, Koji; Kobayashi, Takashi; Fukuzawa, Shigeki; Itoh, Kunihiko (Frontiers in Immunology, 2025)
BackgroundIdiopathic retroperitoneal fibrosis is an IgG4-related disease where pathological role and clinical significance of IgG4 antibodies remain largely unknown. This report shows a rare case of retroperitoneal fibrosis in presence of Autoimmune coagulation factor XIII deficiency, in which an acute life-threatening hemorrhage was successfully managed with effective treatment strategies. Following this, we investigated the molecular mechanisms underlying the patient’s pathology using experimental translational approach.Case presentation and research resultsThe patient was a 60-year-old Asian man with a retroperitoneal mass. A laparoscopic biopsy confirmed that the lesion was retroperitoneal fibrosis with IgG4-expressing plasma cell infiltration. Though biopsy was completed without complications, the patient experienced repeated life-threatening intraperitoneal bleeding starting the next day. Despite performing one emergency laparotomy and three series of emergency transcatheter arterial embolization along with massive transfusions, achieving hemostasis was difficult. Suspecting a humoral autoimmune hemorrhagic disorder, we performed plasma exchange, which achieved complete hemostasis. Later, an abnormal decrease in the activity of coagulation Factor XIII was observed, leading to the diagnosis of Autoimmune coagulation Factor XIII deficiency. Subsequent treatment with steroids and coagulation Factor XIII concentrates prevented further bleeding. We investigated the potential involvement of IgG4-related disease and the effects of IgG4 on coagulation Factor XIII using an in vitro system, and it was demonstrated that both IgG1 and IgG4 recognized the A subunit of coagulation Factor XIII. The purified IgG antibody samples containing IgG1 and IgG4 were shown to significantly reduce the function of coagulation Factor XIII derived from healthy individuals. ConclusionsThe patient experienced recurrent life-threatening bleeding due to Autoimmune coagulation Factor XIII deficiency, which was successfully controlled through plasma exchange therapy. This is the first reported case of concurrent retroperitoneal fibrosis and Autoimmune coagulation Factor XIII deficiency. Based on the results of our research, it is suggested IgG4 may play a role in the pathology of both disorders. It was hypothesized that this hematological disorder could be a part of the spectrum of IgG4 autoimmune diseases.